A comparative study on optimization of the nano magnetic material in recycle fuel oil / Fatihah Wahida Mohd Nor, Muhammad Zahiruddin Ramli and Abdul Hadi Zainal - Mohd Nor, Fatihah Wahida; Ramli, Muhammad Zahiruddin; Zainal, Abdul Hadi (2021)
Quality of recycle fuel oil could be affected by the degradation of storage stability and colour. In this review paper briefly cover the comparison of uses of magnetic particles, Fe3O4 , SiO2, and Al2O3 which is used to determine the fuel stability such as sulphur content, effect of colour degradation and pH analysis by using FTIR, Uv-Vis Spectroscopy and GC-MS. Gas chromatography-mass spectrometry (GC-MS) were used to identify the chemical constituents in the prepared recycle fuel oils (waste lubricants oil). ASTM D1500 were used in order to determine the visuality of a colour from waste lubricants oil and the UV-Vis spectroscopy with 1 cm of optical glass is used for measurement [16]. CaO nano catalyst supported by Fe3O4 magnetic particles were prepared by dissolving the calcium nitrate in deionized water with appropriate amount and 3.5g of Fe3O4 is added into the solution prepared. Then the suspension will be observed until a pH of 12 were appeared. Then, the samples colour was compared with the standard glass colour according to ASTM D1500. Fifteen papers are used as the main references to identify the optimization of nano magnetic material in recycle fuel oil. In conclusion, all the nanomaterial investigated in this present review paper shown the positive result where the quality of recycle fuel oil produced meets the standard. In this present review paper shows that among all the nano material investigated in this present review paper, Fe3O4, SiO2and Al2O3 has great potential to be used as a lowcatalyst in recycle fuel oil (RFO)